STUDI BIOLOGI KUTU DAUN (APHIS GOSSYPII GLOVER) (HEMIPTERA: APHIDIDAE) - Riyanto Riyanto; Djunaidah Zen; Zainal Arifin (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2016)
Abstract: This paper aims at addi information about the biology of aphids (Aphis gossypii Glover) (Hemiptera: Aphididae). A. gossypii biological information include: 1). Imago A. gossypii have winged and wingless. A. gossypii have cauda pale somewhat blackish and two or three pairs of setae hair and have tubercles head apart, front head is relatively flat and there is no protrusion at the base of the antenna. The cornicles of A. gossypii dark color, relatively short and black. A. gossypii have antennae shorter than its body length. Imago A. gossypii wings have black kornikel from the base to the tipsmall tubercles between the antenna and do not have additional protrusions on the dorsal side of the abdomen. The colour of nimfa A. gossypii dispersal from gray to green, sometimes its has a black mark on the head, thorax and abdomen proto-wings and blackish green. Nimfa A. gossypii can develop into winged and wingless imago. The colour of the newly eggsÂ is yellow, but soon becomes shiny black. The eggs are laid on average amounted to 5 eggs per day for 16-18 days. 2). A. gossypii is fitofag cosmopolitan insects which are found in the tropics, subtropics and temperate. A. gossypii have host plants of various families of plants around the world such as Asteraceae, Acanthaceae, Myrtaceae, Solanaceae, Moraceae, Araceae, boraginaceae, Cucurbitacae, Verbenaceae, Sterculiaceae, Rubiaceae, Malvaceae, musaceae, Piperaceae, portulacaceae, Rosaceae, Apocynaceae, Labiatae, Urticeae and Apocynaceae ' Keywords: Aphid, Biology and Aphis gossypii (Glover)